الأحكام القانونية لممارسة الأنشطة التجارية وفقا لتشريع الجزائري - لندة مصوبر; أسماء ماضي (My University, 2021)
Study summary: The commercial registry is a means of engaging in commercial activities, where the extract of this registry includes all the information that belongs to the merchant This is for the purpose of the month of his legal status and the aim of this is to inform the third party who deals with it. This is to achieve the principle of trust and credit, which is the basis of the business transactions. Thus, the commercial registry is considered as an identification card for the trader. whereby each stakeholder may consult him or her with the expenses of such access, which shall be submitted pursuant to an application to the Registrar of the Commercial Registry Centre and so know the legal status of the traders and check their transactions; It also ensures the organization and proper functioning of a human and institutional structure, both at the central and local levels. In the event of a violation of its provisions, civil and criminal liability is incurred. ....................... ملخص الدراسة: يعتبر السجل التجاري وسيلة لممارسة الانشطة التجارية, حيث يتضمن مستخرج هذا السجل كل المعلومات التي تخص التاجر، والمتعلقة بوضعيته ووضعية نشاطه التجاري، وهذا قصد شهر مركزه القانوني و الهدف من ذلك هو إعلام الغير الذي يتعامل معه وهذا لتحقيق مبدأ الثقة والائتمان الذي يعد أساس المعاملات التجارية و بهذا يعتبر السجل التجاري بمثابة بطاقة تعريف للتاجر، حيث يمكن لكل صاحب مصلحة الإطلاع عليه مع تحمل نفقات هذا الاطلاع والذي يكون بموجب طلب يقدم لمأمور مركز السجل التجاري و ذلك لمعرفة الوضعية القانونية للتجار والاطمئنان على معاملاتهم، كما يسهر على تنظيمه وحسن سيره هيكل بشري و مؤسساتي سواءا على المستوى المركزي او على المستوى المحلي، وفي حالة مخالفة احكامه تترتب المسؤولية المدنية و الجزائية. .................... Résumé de l’étude : Le registre commercial est un moyen d’exercer des activités commerciales, lorsque l’extrait de ce registre comprend toutes les informations qui appartiennent au commerçant Ceci est aux fins du mois de son statut juridique et le but de cela est d’informer le tiers qui traite avec elle. Il s’agit de réaliser le principe de confiance et de crédit, qui est la base des transactions commerciales. Ainsi, le registre du commerce est considéré comme une carte d’identification pour le commerçant. par lequel chaque partie prenante peut le consulter sur les frais de cet accès, qui doit être soumis conformément à une demande au registraire du Centre d’enregistrement commercial et ainsi connaître le statut juridique des commerçants et vérifier leurs transactions; Elle assure également l’organisation et le bon fonctionnement d’une structure humaine et institutionnelle, tant au niveau central que local. En cas de violation de ses dispositions, la responsabilité civile et pénale est engagée.